Wheeled Vehicle Toys of the Indus Civilization with Special Reference to Gujarat, India - Vasantha, R.S. (The International Conference on Land Transportation, Locomotive Heritage and Road Culture - 2017, 2017)
Terracotta toy cart frames and wheels provide indirect evidence for the origin and development of wheeled carts based transportation in the alluvial plains of Pakistan and western India around 3500 BC. Evidences from various sites suggest that wheeled cart technology was an indigenous development in Greater Indus region. Excavations of various Harappan sites imply that numerous varieties of wheeled vehicles might have played a key role in the construction of cities and the transport of commodities that were necessary for the establishment and maintenance of large urban centres. The legacy of Harappan carts continued into later periods, and many regional styles of carts used today may have their origins in the ancient Indus cities, towns and villages. Present paper deals with the history and characteristic features of terracotta toy cart frames and wheels from Greater Indus region including Gujarat and issues such as nature of trade and communication networks.
Keywords: Wheel; Indus civilization; Terracotta toy cart